A Cu-based MFI molecular sieve single-atom catalyst prepared by ammonia evaporation and acid treatment strategy and its application

The Cu-based MFI molecular sieve single-atom catalyst prepared by ammonia distillation method and acid treatment strategy solves the problems of low conversion and selectivity and ease of inactivation of existing Cu-based catalysts, achieving high selectivity and high catalytic activity of acetaldehyde and having ultra-high reaction stability.

CN116060098BActive Publication Date: 2025-04-11DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211567415.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-07
Publication Date
2025-04-11
Estimated Expiration
2042-12-07

AI Technical Summary

Technical Problem

The existing non-precious metal Cu-based catalysts have low conversion and selectivity in the ethanol dehydrogenation to acetaldehyde reaction, and the catalysts are prone to deactivate, which limits their industrial applications.

Method used

Cu-based MFI molecular sieve single atom catalyst was prepared by ammonia distillation method and acid treatment strategy. The MFI microporous molecular sieve was used as a support to achieve 100% utilization rate and high activity and high selectivity catalytic conversion of Cu atoms.

Benefits of technology

The high selectivity (more than 97%) and high catalytic activity of acetaldehyde were achieved, and the catalyst could run stably for 240 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116060098B_ABST
    Figure CN116060098B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of ethanol dehydrogenation to acetaldehyde, and specifically relates to a Cu-based MFI molecular sieve single-atom catalyst prepared by an ammonia evaporation method and an acid treatment strategy and its application. The catalyst is represented by the formula Cu-MFI-AM-AC, wherein Cu is an active component, and MFI-AM-AC is a carrier with a multi-level pore structure obtained by carrying the active component Cu and then treating with ammonia evaporation and acid; the active component Cu is dispersed on the carrier in a single-atom state; and the loading amount of the active component Cu in the catalyst is 0.1-2wt%. The catalyst of the present invention realizes the utilization of nearly 100% of copper atoms in the ethanol dehydrogenation to acetaldehyde reaction, and can realize high activity, high selectivity, and high stability of ethanol to generate the target product acetaldehyde under mild conditions, and has significant advantages such as low cost and high atomic utilization rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ethanol dehydrogenation to acetaldehyde, and specifically relates to a Cu-based MFI molecular sieve single-atom catalyst prepared by an ammonia evaporation method and an acid treatment strategy and an application thereof. Background Art

[0002] As an important organic chemical, acetaldehyde has high industrial application value as an intermediate for synthetic medicine and food additives. Its downstream products are many high value-added products, such as acetone, butanol, crotonaldehyde, sorbitol, butadiene and pentaerythritol, which have very wide applications in the chemical industry [Yu Qiannan, Pei Yanpeng, Jiang Na, Mou Zonggang, Li Ping, Li Wenjuan, Wen Qiuhui. Preparation of acetaldehyde by ethanol dehydrogenation catalyzed by supported cobalt carbide catalyst [J]. Journal of Jinan University (Natural Science Edition)]. As the largest consumer of acetaldehyde, my country's acetaldehyde consumption in 2022 will reach about 2 million tons.

[0003] At present, the synthesis methods of acetaldehyde include: ethylene oxidation, acetylene hydration, acetic acid reduction, ethane oxidation, ethanol dehydrogenation, etc. [Mu Jincheng, Zhong Xiang, Liu Jianfang, Qin Rongxian, Ran Zhenzhen, Ji Shengfu. Research progress of ethanol catalytic oxidation, condensation and esterification reactions [J]. Industrial Catalysis, 2018, 26(10): 1-12.]. Compared with the first four preparation processes, ethanol, as a clean and renewable energy, has a wide source and is cheaper. In addition, the non-oxidative dehydrogenation process can also produce hydrogen energy, making it a green and sustainable preparation method. In recent years, the vigorous development of bioethanol technology and the industrial application of coal-to-ethanol with an annual output of 500,000 tons have further enriched the production of ethanol, providing a continuous basis for the process of ethanol dehydrogenation to acetaldehyde.

[0004] The process of ethanol dehydrogenation to acetaldehyde is in line with my country's current energy sustainable strategy and "dual carbon" national policy, and has broad application prospects and industrial value. Although precious metal catalysts such as Au can achieve high conversion rate, high selectivity and high stability of ethanol to acetaldehyde, their high price greatly limits their application in this reaction. Therefore, researchers have vigorously developed non-precious metal catalysts such as Cu and Co. However, the reaction conversion rate and acetaldehyde selectivity of non-precious metal catalysts are low. In addition, non-precious metal catalysts represented by Cu are rapidly deactivated as the particles grow during the reaction, which becomes the shortcoming of Cu-based catalysts in this reaction [Yuan Xiaolu, Huang Yongsheng, Ge Deqiang, Zeng Hui, Wang Jia, Yao Hongtao, Li Xue. Research on the process of ethanol catalytic dehydrogenation to acetaldehyde [J]. Anhui Chemical Industry, 2017, 43(01): 40-42.]. In previous work, we used the ammonia evaporation method to prepare a 20% Cu-MFI catalyst, achieving 97% conversion and 93% selectivity while also obtaining ultra-high stability for 500 hours [Pang J, Zheng M, Wang C, et al. Hierarchical Echinus-like Cu-MFI Catalysts for Ethanol Dehydrogenation [J]. ACS Catalysis, 2020, 10 (22): 13624-13629.]. Although the catalyst achieved excellent reaction performance, the high copper loading in the catalyst caused a large number of Cu centers to be encapsulated, making it unable to play the role of catalytic centers, and also increased the cost of the catalyst. Summary of the invention

[0005] The purpose of the present invention is to provide a Cu-based MFI molecular sieve single-atom catalyst prepared by an ammonia evaporation method and an acid treatment strategy and its application in the reaction of ethanol dehydrogenation to acetaldehyde. Based on MFI microporous molecular sieve as a carrier, a Cu-MFI single-atom catalyst is prepared by combining ammonia evaporation and acid treatment. The single-atom catalyst can achieve 100% Cu atom utilization and high activity and high selectivity of ethanol catalytic conversion to acetaldehyde, and has ultra-high reaction stability, and can stably operate the reaction for 240 hours.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] On one hand, the present invention provides a Cu-based MFI molecular sieve single-atom catalyst prepared by an ammonia evaporation method and an acid treatment strategy. The catalyst is represented by the formula Cu-MFI-AM-AC, wherein Cu is an active component, and MFI-AM-AC is a carrier with a multi-level pore structure obtained by carrying the active component Cu and then subjecting it to ammonia evaporation and acid treatment; the active component Cu is dispersed on the carrier in a single-atom state; and the loading amount of the active component Cu in the catalyst is 0.1-2wt%.

[0008] In the above technical solution, further, the catalyst has a micro-mesoporous structure, the micropore diameter is 0.5-0.7 nm, and the mesopore diameter is 2-10 nm.

[0009] In the above technical solution, further, the catalyst has a specific surface area of ​​300-500m 2 g -1 , internal specific surface area is 100-300m 2 g -1 , external specific surface area is 80-300m 2 g -1 , the micropore volume is 0.1-0.5cm 3 g -1 , the mesopore volume is 0.05-0.2cm 3 g -1 .

[0010] In the above technical solution, further, the loading amount of the active component Cu in the catalyst is 0.5-1.5wt%.

[0011] Another aspect of the present invention provides a method for preparing the above-mentioned Cu-based MFI molecular sieve single-atom catalyst, the method comprising the following steps:

[0012] (1) stirring a soluble salt solution of Cu and a 25 wt% ammonia solution for 20 minutes, then adding MFI molecular sieves and stirring for 3-5 hours;

[0013] (2) heating the mixed solution obtained in step (1) to 60-150° C. and subjecting it to ammonia evaporation for 8-24 hours, so that the ammonia in the solution gradually evaporates until the pH value of the solution reaches neutrality, filtering and separating, drying at 60-200° C. for 6-12 hours, and then calcining in an air atmosphere; the calcination temperature is 300-800° C., and the calcination time is 1-9 hours;

[0014] (3) The mixture obtained in step (2) is treated with 0.5-10 mol / L inorganic acid for 0.5-12 h to obtain the catalyst Cu-MFI-AM-AC.

[0015] In the above technical solution, further, in the step (1), the soluble salt of Cu is one or more of copper nitrate, copper chloride, copper sulfate, copper acetate, and copper acetylacetonate; and the molar ratio of copper to ammonia water is 1:10.

[0016] In the above technical solution, further, in step (2), the temperature of the ammonia evaporation process is 80-120°C, the drying temperature is 100-120°C, the roasting temperature is 400-500°C, and the roasting time is 4-6 hours. The inorganic acid treatment time is 1-4h, and the acid concentration is 1-5mol / L.

[0017] In the above technical scheme, further, in the step (3), the inorganic acid is one or more of nitric acid, hydrochloric acid, acetic acid, and sulfuric acid; the molar ratio of copper to inorganic acid is 1:5; the inorganic acid treatment time is 1-4h, and the inorganic acid concentration is 1-5mol / L.

[0018] In another aspect, the present invention provides an application of the above-mentioned Cu-based MFI molecular sieve single-atom catalyst in the dehydrogenation of ethanol to acetaldehyde, wherein the reaction is carried out in a fixed-bed reactor at atmospheric pressure, and the reaction space velocity range is WHSV=0.2-10h -1 , preferably WHSV = 0.5-5h -1 , using at least one of nitrogen, argon and helium as carrier gas, with a carrier gas space velocity GHSV of 500-100000h -1 , preferably 3000-30000h -1 , the reaction temperature is 200-350°C, preferably 200-300°C.

[0019] The present invention has the following beneficial effects:

[0020] (1) The present invention uses cheap metal Cu as the active component, which is cheaper than traditional precious metal (Au, Ag, etc.) catalysts and has more outstanding industrial prospects.

[0021] (2) The present invention prepares a single-atom catalyst and achieves 100% Cu atom utilization efficiency.

[0022] (3) The catalyst prepared by the strategy of ammonia evaporation and acid treatment in the present invention has a significant multi-level pore structure, excellent anti-carbon deposition ability and mass transfer and diffusion advantages, and exhibits higher operating stability compared to reported molecular sieve catalysts such as Cu / Beta, Cu@S1 and Cu / SBA-15.

[0023] (4) The Cu-MFI-AM-AC catalyst has the advantage of high acetaldehyde selectivity in the ethanol dehydrogenation to acetaldehyde reaction. Under the optimized reaction conditions, the acetaldehyde selectivity can reach more than 97% and maintain high catalytic activity.

[0024] Taking the above factors into consideration, the catalyst of the present invention has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The XRD patterns of the catalysts prepared in Example 1 and Comparative Example 1, wherein a is Comparative Example 1 and b is Example 1;

[0026] Figure 2 N2 physical adsorption diagram of the catalysts prepared in Example 1 and Comparative Example 1;

[0027] Figure 3 The electron microscope images of the catalyst prepared in Example 1, wherein a is the Cu-MFI-AM-AC TEM image, b is the HADDF-STEM image, and c is the Mapping image;

[0028] Figure 4 The stability test results of the catalyst prepared in Example 1 are as follows;

[0029] Figure 5 The results of the stability test of the catalyst prepared in Comparative Example 1 are as follows;

[0030] Figure 6 The results of the stability test of the catalyst prepared in Comparative Example 2 are shown in FIG. DETAILED DESCRIPTION

[0031] The present invention is described in detail below with reference to the embodiments, but the embodiments of the present invention are not limited thereto. Obviously, the embodiments described below are only partial embodiments of the present invention. For those skilled in the art, other similar embodiments obtained without creative labor all fall within the protection scope of the present invention.

[0032] Comparative Example 1

[0033] X%Cu-MFI-AM catalysts with different theoretical Cu loadings were prepared by ammonia evaporation method:

[0034] Step A, mixing ethyl orthosilicate, tetrapropylammonium hydroxide and water in a molar ratio of 1:2:40, stirring at room temperature for 2 hours to obtain a gel;

[0035] Step B, placing the gel into a hydrothermal kettle, and subjecting it to autogenous hydrothermal crystallization at 150° C. in an oven for 3 days;

[0036] Step C, after the crystallization is completed, centrifuge to obtain a white powder, dry at 100°C for 8h, and calcine at 550°C for 4h to obtain an MFI molecular sieve with a microporous structure;

[0037] Step D, dissolving 7.6 g of copper nitrate in 76 g of ammonia water, the mass ratio of copper to ammonia water being 1:10, stirring for 15 minutes, adding 5 g of the above-mentioned microporous structure MFI molecular sieve carrier to react for 4 hours, and then transferring to a 80°C water bath for treatment for 8 hours, the pH of the reaction solution reaches 7, filtering, and drying at 100°C for 8 hours to obtain a 20% Cu-MFI-AM catalyst, and changing the amount of copper nitrate and ammonia water in accordance with the mass ratio of copper to ammonia water to prepare samples with theoretical Cu loadings of 0.1%, 0.2%, 0.5%, 1%, 2%, 5%, 10%, 30% and 40% respectively;

[0038] Step E: calcining the sample in step D at 400° C. in air for 4 h to obtain catalyst X% Cu-MFI-AM with different theoretical Cu loading amounts.

[0039] Comparative Example 2

[0040] The preparation process of 5% Cu / MFI catalyst by impregnation method is as follows: dissolve copper nitrate in water and impregnate it with the microporous structure MFI molecular sieve carrier in equal volume, with the Cu loading amount of 5%, dry at 100℃ for 8h, and then calcine in air at 400℃ for 4h to obtain 5% Cu / MFI catalyst.

[0041] Comparative Example 3

[0042] The 5% Cu / MFI prepared in Comparative Example 2 was post-treated with nitric acid to obtain a 5% Cu / MFI-AC catalyst, wherein 5% is the theoretical content of Cu.

[0043] Comparative Example 4

[0044] The preparation process of 1.1% Cu / MFI catalyst by impregnation method is as follows: copper nitrate is dissolved in water and impregnated with the microporous structure MFI molecular sieve carrier in equal volume, with the Cu loading amount of 1.1%, dried at 100℃ for 8h, and then calcined in air at 400℃ for 4h to obtain 1.1% Cu / MFI catalyst.

[0045] Example 1

[0046] (1) Preparation of X% Cu-MFI-AM catalysts with different theoretical Cu loadings by ammonia evaporation method:

[0047] Step A, mixing ethyl orthosilicate, tetrapropylammonium hydroxide and water in a molar ratio of 1:2:40, stirring at room temperature for 2 hours to obtain a gel;

[0048] Step B, placing the gel into a hydrothermal kettle, and subjecting it to autogenous hydrothermal crystallization at 150° C. in an oven for 3 days;

[0049] Step C, after the crystallization is completed, centrifuge to obtain a white powder, dry at 100°C for 8h, and calcine at 550°C for 4h to obtain an MFI molecular sieve with a microporous structure;

[0050] Step D, dissolving 7.6g of copper nitrate in 76g of ammonia water, the mass ratio of copper to ammonia water being 1:10, stirring for 15 minutes, adding 5g of the microporous structure MFI molecular sieve carrier prepared in step C to react for 4h, then transferring to a water bath at 80°C for treatment for 8h, the pH of the reaction solution reaches 7, filtering, and drying at 100°C for 8h to obtain a 20% Cu-MFI-AM catalyst, and changing the amount of copper nitrate and ammonia water in accordance with the mass ratio of copper to ammonia water to prepare samples with theoretical Cu loadings of 0.1%, 0.2%, 0.5%, 1%, 2%, 5%, 10%, 30% and 40% respectively;

[0051] Step E, calcining the sample obtained in step D at 400° C. in air for 4 h;

[0052] (2) Preparation of X% Cu-MFI-AM-AC catalyst by pickling:

[0053] The sample obtained in step E was treated with acid in 100 g nitric acid (6 mol / L) for 2 h, and then calcined in air at 400° C. for 4 h to obtain Cu-MFI-AM-AC catalysts with different theoretical Cu loadings of X%.

[0054] The catalysts with different theoretical Cu loadings prepared in Example 1 and Comparative Example 1 were subjected to ICP quantitative analysis of Cu content. The actual loading amount of Cu, the active component of the catalyst, is shown in Table 1.

[0055] Table 1

[0056] catalyst Before acid treatment (wt%) After acid treatment (wt%) 2%Cu-MFI-AM 1.9 0.2 5%Cu-MFI-AM 5.1 1.1 10%Cu-MFI-AM 9.5 0.5 20%Cu-MFI-AM 19.3 0.6 30%Cu-MFI-AM 28.7 0.5 40%Cu-MFI-AM 37.1 0.2 5%Cu / MFI 5.3 1.6

[0057] The physical structure of Cu-MFI-AM before and after nitric acid treatment was investigated by XRD, N2-physical adsorption, and HRTEM, further revealing the simplicity and effectiveness of the ammonia vaporization-acid treatment strategy for constructing hierarchical pore molecular sieve catalysts.

[0058] The XRD patterns of Cu-MFI-AM catalyst before and after nitric acid treatment are shown in Figure 1 As shown, the N2 physical adsorption diagram is as follows Figure 2 The pore structure properties are shown in Table 2.

[0059] Table 2

[0060]

[0061]

[0062] XRD results show that acid treatment does not destroy the crystal structure of the carrier MFI molecular sieve. Combined with the N2 isothermal adsorption-desorption curve, it can be seen that after acid treatment, the adsorption curve type changes from type I (microporous type) to type IV (mesoporous type). Further combined with the pore structure distribution results in the table, the pore size of the catalyst changes from the original 3nm to 6nm through acid treatment. In addition, the pore volume and specific surface area of ​​the mesopores are gradually increasing. The ammonia-acid treatment method is an effective way to construct a multi-level pore structure.

[0063] Electron microscopy results show that Cu on the catalyst exists in the form of single atoms rather than nanoparticles, indicating that the ammonia-acid treatment method is an effective strategy for preparing single-atom catalysts.

[0064] Example 2

[0065] Preparation of Cu-MFI-AM-AC catalyst with a theoretical Cu loading of 5% at different calcination temperatures: The preparation process is similar to that of Example 1, except that the calcination temperatures are 300°C, 500°C, 600°C, 700°C, and 800°C, respectively.

[0066] Test Example 1

[0067] Evaluation process of ethanol dehydrogenation to acetaldehyde catalyst: 0.5 g of the Cu-MFI-AM-AC catalyst prepared in Example 1 was pelletized and loaded into a fixed bed reactor. The ethanol raw material was brought into the reactor by pump feeding and carrier gas (flow rate of 100 mL / min). The reaction space velocity was WHSV=1 h -1 , the reaction temperature is 250℃.

[0068] Reaction conversion and selectivity calculation method:

[0069] Ethanol conversion rate (%) = (n 反应前的乙醇 -n 反应后剩余乙醇 ) / n 反应前的乙醇 *100%

[0070] Acetaldehyde selectivity (%) = n 产物中乙醛 / (n 反应前的乙醇 -n 反应后剩余乙醇 )*100%

[0071] The performance evaluation of X%Cu-MFI-AM-AC catalysts with different theoretical Cu loadings is shown in Table 3.

[0072] Table 3

[0073] catalyst Ethanol conversion rate (%) Acetaldehyde selectivity (%) 2%Cu-MFI-AM-AC 69 75 5%Cu-MFI-AM-AC 85 97 10%Cu-MFI-AM-AC 71 85 20%Cu-MFI-AM-AC 73 82 30%Cu-MFI-AM-AC 68 83 40%Cu-MFI-AM-AC 65 80

[0074] From the reaction results, it can be seen that when the theoretical loading of Cu is 5%, that is, the actual loading is 1.1%, it has excellent catalytic performance when acid treatment is performed.

[0075] Test Example 2

[0076] The performance evaluation of the 5% Cu-MFI-AM-AC catalyst with a theoretical Cu loading of 5% in Example 1 and the X% Cu-MFI-AM catalyst with different theoretical Cu loadings in Comparative Example 1 was compared. The reaction conditions were the same as those in Test Example 1.

[0077] Table 4

[0078] catalyst Ethanol conversion rate (%) Acetaldehyde selectivity (%) 0.1%Cu-MFI-AM 16 43 0.2%Cu-MFI-AM 19 85 0.5%Cu-MFI-AM 31 55 1%Cu-MFI-AM 42 70 2%Cu-MFI-AM 54 76 5%Cu-MFI-AM 73 68 5%Cu-MFI-AM-AC 85 97

[0079] It can be seen from the table that the catalyst using the acid treatment strategy has obvious advantages and can significantly improve the selectivity of acetaldehyde.

[0080] Test Example 3

[0081] The catalytic performance of 5%Cu-MFI-AM-AC catalyst with a theoretical Cu loading of 5% was investigated at different reaction temperatures, and the other reaction conditions were the same as those in Test Example 1.

[0082] Table 5

[0083] Reaction temperature (℃) Ethanol conversion rate (%) Acetaldehyde selectivity (%) 200 30 99 225 57 99 250 85 97 275 90 90 300 98 87 350 100 75

[0084] It can be seen from the table that the catalyst provided by the present invention can produce the target product acetaldehyde under the reaction conditions of 200-350°C, the preferred reaction temperature is 200-300°C, and the optimal temperature is 250°C.

[0085] Test Example 4

[0086] The catalytic performance of 5% Cu-MFI-AM-AC with a theoretical Cu loading of 5% was investigated at different calcination temperatures, and the reaction conditions were the same as those in Test Example 1.

[0087] Table 6

[0088] Calcination temperature (℃) Ethanol conversion rate (%) Acetaldehyde selectivity (%) 300 43 78 400 85 97 500 88 90 600 80 76 700 72 59 800 61 45

[0089] It can be seen from the table that the catalyst provided by the present invention can stably exist and produce the target product acetaldehyde under the condition of a calcination temperature of 300-800°C, and the preferred calcination temperature is 400-500°C.

[0090] Test Example 5

[0091] Comparison of catalyst stability:

[0092] To further highlight the superiority of the present invention, the stability of 5% Cu-MFI-AM-AC with a theoretical Cu loading of 5% was investigated, and the stability of 5% Cu-MFI-AM catalyst with a theoretical Cu loading of 5% without acid treatment and 5% Cu / MFI catalyst with a theoretical Cu loading of 5% by impregnation method were compared. Figure 4-6 shown.

[0093] Although the 5% Cu-MFI-AM catalyst without acid treatment has high activity, its acetaldehyde selectivity and stability are significantly worse than those of the single-atom catalyst after acid treatment, and its reaction stability is significantly inferior to that of the 5% Cu-MFI-AM-AC catalyst. In addition, the activity and selectivity of the 5% Cu / MFI catalyst prepared by the impregnation method, as well as its reaction stability are significantly inferior to those of the 5% Cu-MFI-AM-AC obtained by the distilled ammonia-acid treatment. This indicates that the single-atom catalyst constructed by the distilled ammonia-acid treatment of the present invention has unique novelty and superiority in reaction stability.

[0094] The 5% Cu / MFI catalyst prepared by the impregnation method was further subjected to nitric acid post-treatment, and the catalyst was labeled as 5% Cu / MF-AC. Considering that the actual Cu content of the 5% Cu-MFI-AM-AC catalyst subjected to nitric acid post-treatment is 1.1%, the 1.1% Cu / MFI catalyst prepared by the impregnation method was further used as a comparison. The corresponding catalytic performance was examined to further highlight the superiority of the catalyst of the present invention, and the reaction conditions were the same as those in Test Example 1.

[0095] Table 7

[0096] catalyst Ethanol conversion rate (%) Acetaldehyde selectivity (%) 5%Cu-MFI-AM-AC 85 97 5%Cu / MFI 70 85 5%Cu / MFI-AC 15 60 1.1%Cu / MFI 23 63

[0097] From the results in the above table, it can be seen that the conversion rate and acetaldehyde selectivity of the 5% Cu / MFI catalyst prepared by the impregnation method and the catalyst post-treated with nitric acid in the reaction are reduced, indicating that the single-atom catalyst 5% Cu-MFI-AM-AC constructed by the ammonia evaporation-acid treatment strategy of the present invention has high ethanol conversion rate and acetaldehyde selectivity.

[0098] In summary, the Cu single-atom catalyst Cu-MFI-AM-AC constructed by the ammonia evaporation-acid treatment strategy in the present invention can be used for the dehydrogenation of ethanol to produce acetaldehyde. The catalyst prepared by this strategy has the advantages of good activity, high acetaldehyde selectivity, 100% atomic utilization, and low cost.

Claims

1. A Cu-based MFI molecular sieve single-atom catalyst prepared by an ammonia distillation method and an acid treatment strategy, characterized in that: The catalyst is represented by the formula Cu-MFI-AM-AC, wherein Cu is an active component, MFI-AM-AC is a carrier having a multi-level pore structure obtained by carrying the active component Cu and then treating with ammonia evaporation and acid; the active component Cu is dispersed on the carrier in a single-atom state; and the loading amount of the active component Cu in the catalyst is 0.1-2wt%; The preparation method of the catalyst comprises the following steps: (1) stirring a soluble salt solution of Cu and a 25 wt% ammonia solution for 20 minutes, then adding MFI molecular sieves and stirring for 3-5 hours; (2) heating the mixed solution obtained in step (1) to 60-150° C. and subjecting it to ammonia evaporation for 8-24 hours, so that the ammonia in the solution gradually evaporates until the pH value of the solution reaches neutrality, filtering and separating, drying at 60-200° C. for 6-12 hours, and then calcining in an air atmosphere; the calcination temperature is 300-800° C., and the calcination time is 1-9 hours; (3) The mixture obtained in step (2) is treated with 0.5-10 mol / L inorganic acid for 0.5-12 h to obtain a Cu-based MFI molecular sieve single atom catalyst.

2. The catalyst according to claim 1, characterized in that: The catalyst has a micro-mesoporous structure, the micropore diameter is 0.5-0.7 nm, and the mesopore diameter is 2-10 nm.

3. The catalyst according to claim 1, characterized in that: The specific surface area of ​​the catalyst is 300-500m 2 g -1 , internal specific surface area is 100-300m 2 g -1 , external specific surface area is 80-300m 2 g -1 , the micropore volume is 0.1-0.5cm 3 g -1 , the mesopore volume is 0.05-0.2cm 3 g -1 .

4. The catalyst according to claim 1, characterized in that: The loading amount of the active component Cu in the catalyst is 0.5-1.5wt%.

5. The catalyst according to claim 1, characterized in that: In the step (1), the soluble salt of Cu is one or more of copper nitrate, copper chloride, copper sulfate, copper acetate, and copper acetylacetonate; and the molar ratio of copper to ammonia water is 1:

10.

6. The catalyst according to claim 1, characterized in that: In the step (2), the temperature of the ammonia evaporation process is 80-120°C; the drying temperature is 100-120°C; the roasting temperature is 400-500°C, and the roasting time is 4-6 hours; the inorganic acid treatment time is 1-4h, and the acid concentration is 1-5mol / L.

7. The catalyst according to claim 1, characterized in that: In the step (3), the inorganic acid is one or more of nitric acid, hydrochloric acid, acetic acid, and sulfuric acid; the molar ratio of copper to inorganic acid is 1:5; the inorganic acid treatment time is 1-4h, and the inorganic acid concentration is 1-5mol / L.

8. An application of the Cu-based MFI molecular sieve single-atom catalyst according to any one of claims 1 to 7 in the reaction of ethanol dehydrogenation to acetaldehyde, characterized in that: The reaction is carried out in a fixed bed reactor at atmospheric pressure, and the reaction space velocity range is WHSV = 0.2-10h -1 , using at least one of nitrogen, argon and helium as carrier gas, with a carrier gas space velocity GHSV of 500-100000h -1 , the reaction temperature is 200-350℃.

9. The use according to claim 8, characterized in that: The reaction temperature is 200-300°C, and the reaction space velocity range is WHSV=0.5-5h -1 , carrier gas space velocity is 3000-30000h -1 .

Citation Information

Patent Citations

  • Preparation method and application of catalyst for preparing acetaldehyde through ethanol dehydrogenation

    CN114054079A